2018
DOI: 10.3390/nu10101413
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Long Chain Omega-3 Polyunsaturated Fatty Acids on Brain Function in Mildly Hypertensive Older Adults

Abstract: Purported benefits of long chain omega-3 polyunsaturated fatty acid (LCn-3PUFA) for brain function may be attributable, at least in part, to improved cerebral perfusion. A pilot randomised controlled trial was undertaken to investigate effects of taking a DHA-rich fish oil supplement for 20 weeks on cerebrovascular function, mood and cognitive performance. Borderline hypertensives aged 40–85 years with low habitual LCn-3PUFA intake took four capsules/day of EPAX (1600 mg DHA + 400 mg EPA) or placebo (corn oil)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
(34 reference statements)
3
18
1
2
Order By: Relevance
“…To our knowledge, we are the first to report this potential connection between omega-3 supplementation and improved CBF measures during exercise. However, this finding is consistent with randomized controlled trials that have found that omega-3 supplementation can increase CBF during other cerebrovascular challenges such as hypercapnia and cognitive tasks [4,6].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…To our knowledge, we are the first to report this potential connection between omega-3 supplementation and improved CBF measures during exercise. However, this finding is consistent with randomized controlled trials that have found that omega-3 supplementation can increase CBF during other cerebrovascular challenges such as hypercapnia and cognitive tasks [4,6].…”
Section: Discussionsupporting
confidence: 89%
“…Future studies that measure changes in CBF would provide evidence for this mechanistic pathway. Importantly, one randomized trial lends credence to this potential mechanism by showing that 20 weeks of omega-3 supplementation increased CBF response to carbon dioxide and cognitive tasks in older adults with borderline hypertension [6]. The current study expands upon these findings by demonstrating preserved exercising CBF velocity with age with omega-3 supplementation, specifically in older adults who are at increased risk for vascular dysfunction.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The supplement group did not show any increase in brain volume. Howe, Evans, Kuszewski and Wong [103] administered fish oil supplement in a randomized control trial for 20 weeks in a group of older adults. There was some structural change observed-cerebrovascular responsiveness to hypercapnia, but only in women.…”
Section: Discussionmentioning
confidence: 99%